Butterfly Fauna in Similipal Biosphere Reseve, Mayurbhanj, North Orissa, India - Sethy, P. G. S.; Sahu, Prajyoti; Siddiqi, S. Z. (Indian Forester, 2007)
The present study highlights the species diversity in butterfly fauna [Lepidoptera : Rhopalocera] in terms of species richness and equitability, in Similipal Biosphere Reserve, Mayurbhanj, North Orissa. The study was based upon field studies/observation, through random survey, from 39 randomly selected sampling sites (buffer/core areas) during different seasons in the sprawling 2750 km2 of protected area. Earlier study records 27 species of butterflies, under 17 genera and 6 families, among other fauna, from the Biosphere Reserve, while the present inventory, takes the total to 52 species, under 32 genera and 5 families. Of these, family Nymphalidae (26 species) is well represented throughout, occurring commonly, followed by Papilionidae (15 species), Pieridae (6 species), Lycaenidae(2 species) and Hesperiidae (3 species), Further, the study also extends the range of distribution of 25 species to the protected area, with notes on their habitat, besides adding 13 species to the state lepidopteran fauna.